Isolated metacarpal bone metastasis from advanced rectosigmoid carcinoma - AR, Fadli; Md Nor, Azmi; O., David; Mat Hassan, Mohd. Zailani (Faculty of Medicine, International Islamic University Malaysia, 2012)
Distant metastasis is a common sequelae of stage III colorectal adenocarcinoma. Liver and lungs are the most common sites for distant metastases, but, metastases to extremities are very rare. We report a case of rectosigmoid adenocarcinoma, which metastasizes to left first metacarpal bone, which is the first occurrence in our experience. The investigations and management of the patient are discussed.